MİSOPROSTOL İLE OKSİTOSİN VE METİLERGOBASİN MALEAT KULLANIMININ DOĞUMUN ÜÇÜNCÜ DÖNEMİNİN SÜRESİNE VE KAN KAYBINA OLAN ETKİLERİNİN KARŞILAŞTIRILMASI - SAPMAZ, Ekrem; BULGAN, Esra; AY, Gül (Cerrahpaşa Medical Journal, 2014)
Background.- The comparison of the effects of mysoprostole (800 mcg/PO) or oxytosine 10 IU/IM. plus methylergobacine maleate (200 mg/IM) administered in the third stage of labor on the duration of the stage and blood loss. Design.- Seventy pregnants admitted to department of Obstetrics and Gynecology were randomly selected to this prospective and single blind study program. Right after labor, umblical cord was clamped and mysoprostole 800 mcg/PO were administered to the individuals in the study group (group 1) and oxytosine 10 IU plus methylergobacine maleate 200 mcg/IM in the control group (group 2). The parameters relating the third stage blood loss before and after the delivery of placenta; the duration of third stage was monitored. The monitoring of the side effects has been done by checking body temperature, shivering, noisea . vomiting, diarrhea, blood pressure every hour for the first day after the cord was clamped. Body temperatures over 38 0C were accepted meaningful (<38 0C=0 p, >38 0C=1p) and nominal scale was employed for the alterations in noisea . vomiting, diarrhea (absent=0p, present=1p) and blood pressure (systolic>150 mmHg, diastolic>100 mmHg=1p, if both below the given values=0p). Results.- Study was accomplished in 66 patients. Blood loss after the delivery of placenta was found to be 57±6 ml in group 1, whereas it was 161±87 ml in group 2 (p<0.001, Student t test). The duration of the third stage of labor was found as 5.7±1.5 min in group 1, whereas it was 18±5 min in group 2 (p<0.001, Student.s t test). Body temperature elevations were encountered in all 33 cases (100%) in group 1 and in 4 cases (12%) in group 2 (RR=8, p<0.001, Fisher’s exact test). Shivering was found in 33 cases (100%) in group 1 and in 9 cases (27%) in group 2. (RR=3.7, p=0.001, Fisher’s exact test). Total blood loss was below 500 ml in 31 cases (93%) in group 1 and in 23 cases (70%) in group 2 (RR=1.3, p<0.001, Fisher’s exact test). Conclusion.- In contrary to oxytosine plus methergine, mysoprostole administered in the third stage of labor, diminishes the duration of third stage and blood loss, as well as elevates the body temperature and promotes shivering. But it may well be an alternative to oxytosine plus methergine due to blood loss decreasing effect and the ease in its storage and application.